Second chorus - Potter, H. C. (Henry C.), 1904-1977; Astaire, Fred; Goddard, Paulette, 1911-1990; Paramount Pictures, Inc.; Cinetel Films ([Hollywood, CA] : Paramount Pictures, Inc., 1940)
Danny and Hank are surprised when Artie Shaw hires competent manager Ellen away from their college band. The two trumpet players scheme to get into Shaw's outfit themselves, each trying to trump the other's plays. --
Fred Astaire, Paulette Goddard, Artie Shaw and Orchestra, Charles Butterworth, Burgess Meredith.
Director of photography, Theodor Sparkuhl; editor, Jack Dennis; music, Artie Shaw.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 14, 2015).
Keywords: Musicians -- Drama; Big bands -- Drama; Comedy films; Musical films; Feature films; Internet videos; Streaming video